Karakterizacija krom-nitridne prevleke, nanesene na nerjavno jeklo s postopkom IBAD - Zalar, Anton (Vakuumist, 1999)
Chromium-nitride coatings can provide a hard, wear-resistent surface for stainless steel components. In the frames of the Co-ordinated Research Program on the "Modification of Materials by Ion Treatment for Industrial Applications", organized by the International Atomic Energy Agency, the chromium-nitride coating on stainless steel (SS304) was characterized in twelve different laboratories. Here we report on the results obtained in the Laboratory of surface and thin film analysis at the Institute of Surface Engineering and Optoelectronics. The stainless steel substracts were coated with about 1mum thick nonstoichiometric CrN. The samples were prepared by Spire Corporation of Bedford, Massachusetts in USA, using the Ion Beam Assisted Deposition (IBAD) technique. The polished stainless steel substrates were coated in one batch using rotational and translational substrate holders to achieve uniform coating thickness and composition. Chromium was evaporated with an electron gun while nitrogen was supplied to the coating by an ion gun. For the characterization and analytical testing we performed Auger electron spectroscopy (AES), X-ray photoelectron spectroscopy and atomic force microscopy (AFM).
Keywords: tanke plasti; prevleke; površine; kromov nitrid; karakterizacija